Preparation method of multi-scale porous electrode with high activity and high conductivity

By using selective laser melting 3D printing technology on the OER electrocatalytic electrode, and electrochemical activation treatment, the problems of smooth electrode surface, low activity and low conductivity are solved, and efficient OER reaction and long-term stability of the electrode are achieved.

CN119507018AActive Publication Date: 2025-02-25HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411694266.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing OER electrocatalytic electrode has smooth surfaces, low activity and low conductivity, making it difficult to meet the needs of efficient electrolytic oxygen evolution reactions.

Method used

The micron-scale porous electrode support structure was prepared by 3D printing technology of selective laser melting, and the surface of the electrode material was modified through the constant voltage electrochemical activation process to form a nanoscale microscopic rough surface morphology.

Benefits of technology

The high activity and high conductivity of multi-scale porous electrodes are achieved, and the OER reaction with high current density can be achieved at low overpotentials and maintain stability during long working hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507018A_ABST
    Figure CN119507018A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a multi-scale porous electrode with high activity and high conductivity, and relates to a preparation method of a multi-scale porous electrode with high activity and high conductivity. The invention aims to solve the technical problems of smooth surface, low activity and low conductivity of the existing OER electro-catalysis electrode. According to the preparation method, selective laser melting is firstly used for carrying out a 3D printing preparation process of an electrode support, then an electrolyte activation solution is used for carrying out secondary treatment, which is called as in-situ electrochemical activation treatment, so that composite preparation of a multi-scale porous electrode is realized; the flatness of the original smooth porous electrode surface is damaged, the electrode supporting surface is roughened, the electrode surface presents a nanoscale microstructure morphology, the surface structure enables the specific surface area of the electrode structure to be multiplied, activation sites of chemical reaction are further increased, and the chemical reaction efficiency is improved. And the electronic conductivity of the electrode and the electrocatalytic activity applied to large-current electrolysis can be enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a multi-scale porous electrode with high activity and high conductivity. Background Art

[0002] With the global governance of environmental pollution, it is necessary to develop clean and renewable energy and improve energy utilization, which is reflected in the electrolysis of water to produce hydrogen and oxygen. At present, the low energy efficiency of the anode oxygen evolution reaction (OER) makes the energy output utilization rate very low. Optimizing the electrode structure and developing highly active OER electrocatalytic electrodes are of great significance to reduce the anode energy barrier to improve energy efficiency. In order to achieve high current density oxygen evolution electrocatalysis for industrial applications, OER electrodes need to meet multiple characteristics at the same time: high intrinsic activity and large effective electrochemical active surface area, high conductivity, rapid transport of electrolytes and bubbles, and good corrosion resistance under strong oxidizing conditions. Traditional electrochemical catalytic electrodes have a nearly smooth surface and a relatively low reaction rate during the reaction process. Summary of the invention

[0003] The present invention aims to solve the technical problems of the smooth surface, low activity and low conductivity of the existing OER electrocatalytic electrode, and to provide a method for preparing a multi-scale porous electrode with high activity and high conductivity.

[0004] The method for preparing the multi-scale porous electrode with high activity and high conductivity of the present invention is carried out according to the following steps:

[0005] 1. Use selective laser melting 3D printing technology to prepare a micron-scale porous electrode support structure. The porous electrode support structure can achieve a micron-scale pore structure morphology, and the overall support and frame are also micron-scale structures;

[0006] 2. placing the porous electrode support structure prepared in step 1 into an electrolyte solution for constant voltage electrochemical activation process to modify the surface of the electrode material, thereby preparing a nanoscale micro-rough surface morphology, and then washing the electrode in a deionized water solution for multiple times, and finally drying it to obtain a multi-scale porous electrode;

[0007] The electrolyte solution is an aqueous solution of ammonium chloride.

[0008] The present invention first uses selective laser melting (SLM) to perform a 3D printing preparation process for electrode supports. In the second step, a self-developed electrolyte activation solution is used for secondary treatment, which is called in-situ electrochemical activation treatment, to achieve the composite preparation of multi-scale porous electrodes. After the constant voltage in-situ electrochemical activation process, the flatness of the originally smooth porous electrode surface is destroyed, the electrode support surface becomes rough, the electrode surface presents a nanoscale microstructure morphology and the electrode support surface has a layer of electrochemical activation layer, and the nanoscale microstructure is shown in the scanning electron microscope (SEM) analysis test. This surface structure doubles the specific surface area of ​​the electrode structure and further increases the activation site of the chemical reaction, which can enhance the electronic conductivity of the electrode and the electrocatalytic activity of the large current electrolysis application. In addition, the increase in specific surface area can obtain a large surface and a strong porous electrode support with less material consumption.

[0009] The multi-scale porous electrode prepared by the present invention exhibits excellent electrochemical activity and high conductivity, and has good durability at low overvoltage potential, and can realize ultra-large current electrolysis of water and oxygen evolution reaction, which largely meets the requirements of high-activity OER reaction, reduces loss, and improves energy efficiency. The technical route and working principle schematic diagram of the present invention are shown in FIG. Figure 1 shown.

[0010] The multi-scale porous electrode of the present invention can still maintain a reaction activity equivalent to that of the initial reaction and exhibit excellent stability after undergoing multiple cycles under optimal high current working conditions.

[0011] The multiscale porous electrode prepared by the present invention is used for OER catalysis, and a low overpotential of 1.4 A cm is achieved at 290 mV to 300 mV. -2 ~1.6A·cm -2 It can maintain good stability at high current density during the working time of nearly 50h.

[0012] The present invention selects NH 4 As an electrolyte, Cl aqueous solution is weakly acidic and can ionize ammonium ions and chloride ions. As a strong electrolyte solution, it is corrosive to most metals. 4 The aqueous solution of F has stronger corrosive properties, and Cl - It has stronger penetrating ability and can penetrate the oxide layer on the metal surface more quickly, reacting with the metal to form soluble compounds, causing changes in the metal surface structure and corroding the metal.

[0013] The present invention opens the door to large-scale industrial water electrolysis and provides new possibilities for the preparation of large-scale production and long-term use of electrocatalytic reaction electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic diagram of the technical route and working principle of the present invention;

[0015] Figure 2 This is a low-magnification SEM image of the surface of the multi-scale porous electrode prepared in Experiment 1;

[0016] Figure 3 This is a high-magnification SEM image of the surface of the multi-scale porous electrode prepared in experiment 1. DETAILED DESCRIPTION

[0017] Specific implementation method 1: This implementation method is a method for preparing a multi-scale porous electrode with high activity and high conductivity, which is specifically carried out according to the following steps:

[0018] 1. Prepare micron-scale porous electrode support structure using selective laser melting 3D printing technology;

[0019] 2. placing the porous electrode support structure prepared in step 1 into an electrolyte solution for constant voltage electrochemical activation process to modify the surface of the electrode material, thereby preparing a nanoscale micro-rough surface morphology, and then washing the electrode in a deionized water solution for multiple times, and finally drying it to obtain a multi-scale porous electrode;

[0020] The electrolyte solution is an aqueous solution of ammonium chloride.

[0021] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the material of the micron-scale porous electrode support structure described in step 1 is Ti-based alloy material, Au, Ag or Cu. The rest is the same as specific implementation method 1.

[0022] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the 3D printing technology of selective laser melting in step one is combined with modeling software to model the micron-level porous structure, and then the subsequent printing process is performed to prepare the required micron-level porous electrode structure, and the structure of the micron-level holes can be a porous lattice structure with a regular configuration, or a porous structure with an irregular minimal curved surface. The rest is the same as specific implementation method one or two.

[0023] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the concentration of the aqueous ammonium chloride solution in step 2 is 0.2 mol / L to 0.8 mol / L. The rest is the same as specific embodiments 1 to 3.

[0024] Specific embodiment 5: This embodiment differs from specific embodiment 4 in that: in step 2, before the constant voltage electrochemical activation process, the porous electrode support structure prepared in step 1 is first placed in anhydrous ethanol, acetone and deionized water for ultrasonic cleaning respectively, and finally dried. The rest is the same as specific embodiment 4.

[0025] Specific embodiment 6: This embodiment differs from specific embodiment 5 in that: the constant voltage electrochemical activation process in step 2 is to place the porous electrode support structure in the electrolyte solution and use a three-electrode device to perform an in-situ electrochemical activation process on the porous electrode surface. Other aspects are the same as specific embodiment 5.

[0026] Specific embodiment 7: This embodiment differs from specific embodiment 6 in that: in the three-electrode device described in step 2, graphite or carbon rod is used as the counter electrode, Pt is used as the reference electrode, and the porous electrode support structure is used as the working electrode. The rest is the same as specific embodiment 6.

[0027] Specific embodiment eight: This embodiment differs from specific embodiment seven in that: in the constant voltage electrochemical activation process described in step two, a constant voltage of 1.38V to 1.47V is applied, and the activity time is 4h to 6h, and a rough nanostructure with a thickness of 1 to 3nm can be observed on the porous electrode support surface in step one, and a multi-scale porous electrode structure is obtained. The rest is the same as specific embodiment seven.

[0028] Specific embodiment 9: This embodiment is different from specific embodiment 8 in that the drying temperature in step 2 is 60° C. to 100° C. The rest is the same as specific embodiment 8.

[0029] Specific embodiment 10: This embodiment is different from specific embodiment 9 in that the drying time in step 2 is 2 hours. Other aspects are the same as specific embodiment 9.

[0030] The present invention is verified by the following tests:

[0031] Experiment 1: This experiment is a method for preparing a multi-scale porous electrode with high activity and high conductivity, which is specifically carried out in the following steps:

[0032] 1. Prepare micron-scale porous electrode support structure using selective laser melting 3D printing technology;

[0033] The material of the micron-scale porous electrode support structure is 316L stainless steel;

[0034] The selective laser melting 3D printing technology combines modeling software to model micron-scale porous structures, and then performs a subsequent printing process to prepare the required micron-scale porous electrode structure;

[0035] 2. The porous electrode support structure prepared in step 1 is placed in anhydrous ethanol, acetone and deionized water for ultrasonic cleaning respectively, and finally dried, and then placed in an electrolyte solution for constant voltage electrochemical activation process to modify the surface of the electrode material to prepare a nanoscale micro-rough surface morphology, and then the electrode is washed in a deionized water solution for many times, and finally dried at 80° C. for 2 hours to obtain a multi-scale porous electrode;

[0036] The electrolyte solution is an ammonium chloride aqueous solution, and the concentration of the ammonium chloride aqueous solution is 0.5 mol / L;

[0037] The constant voltage electrochemical activation process in step 2 is to place the porous electrode support structure in an electrolyte solution and use a three-electrode device to perform an in-situ electrochemical activation process on the surface of the porous electrode, wherein graphite is used as a counter electrode, Pt is used as a reference electrode, and the porous electrode support structure is used as a working electrode.

[0038] The constant voltage electrochemical activation process described in step 2 applies a constant voltage of 1.4 V and the activation time is 5 hours.

[0039] Figure 2 This is a low-magnification SEM image of the surface of the multi-scale porous electrode prepared in Experiment 1. Figure 3 This is a high-magnification SEM image of the surface of the multi-scale porous electrode prepared in Experiment 1. 4 In-situ electrochemical activation in Cl electrolyte solution generates a nanoscale rough structure on the electrode surface and grows very densely, and the porous electrode support structure has a large surface area, which is of great significance for the preparation of an effectively activated electrolyte solution; the top area of ​​the electrode activation layer is a porous structure with a dense interface and no visible defects, and the activation layer is firmly bonded to the 3D printed support. 4 The Cl solution is beneficial to the roughening of the electrode surface and strongly increases the active surface area of ​​the electrode, so that a higher current density and higher activity can be obtained during the reaction.

[0040] Experiment 2: Electrochemical testing of the multi-scale porous electrode prepared in Experiment 1 was performed with a scan rate of 0.2 mV s -1 When iR compensation is 85%, the electrochemically activated multi-scale porous electrode can reach nearly 350mAcm at the fastest speed when the voltage is 1.2V to 1.6V. -2 of current density.

[0041] Study the current density during the reaction, corresponding to current density 10 ~ 50mAcm -2Under the overpotential conditions, it was found that the current density of the multi-scale porous electrode obtained in experiment 1 increased, the reaction overpotential decreased, and the in situ electrochemical activation enhanced the OER reaction activity.

[0042] The multi-scale porous electrode prepared in Experiment 1 has an extremely high current density at ultra-low overpotential during the OER reaction. The high current density achieved by the present invention reaches 1.4A·cm -2 ~1.6A·cm -2 , the overpotential is 290mV~300mV.

[0043] Achieving stability at high current density: The multiscale porous electrode prepared in Experiment 1 was found to be able to maintain a high current density (1.4 A cm) for nearly 50 h during OER catalysis. -2 ~1.6A·cm -2 ) stable working state, the working potential does not fluctuate significantly; and after high current and long-term electrocatalytic testing, SEM observation shows that there is no obvious change in the nano-scale structure of the electrode surface, and there is no obvious change in the electrode composition and chemical state.

Claims

1. A method for preparing a multi-scale porous electrode with high activity and high conductivity, characterized in that The preparation method of the multi-scale porous electrode with high activity and high conductivity is carried out as follows:

1. Prepare micron-scale porous electrode support structure using selective laser melting 3D printing technology; 2. placing the porous electrode support structure prepared in step 1 into an electrolyte solution for constant voltage electrochemical activation process to modify the surface of the electrode material, thereby preparing a nanoscale micro-rough surface morphology, and then washing the electrode in a deionized water solution for multiple times, and finally drying it to obtain a multi-scale porous electrode; The electrolyte solution is an aqueous solution of ammonium chloride.

2. The method for preparing a multi-scale porous electrode with high activity and high conductivity according to claim 1, characterized in that The material of the micron-scale porous electrode support structure described in step 1 is Ti-based alloy material, Au, Ag or Cu.

3. The method for preparing a multi-scale porous electrode with high activity and high conductivity according to claim 1, characterized in that In step 1, the selective laser melting 3D printing technology is combined with modeling software to model the micron-scale porous structure, and then a subsequent printing process is performed to prepare the required micron-scale porous electrode structure.

4. The method for preparing a multi-scale porous electrode with high activity and high conductivity according to claim 1, characterized in that The concentration of the aqueous ammonium chloride solution described in step 2 is 0.2 mol / L to 0.8 mol / L.

5. The method for preparing a multi-scale porous electrode with high activity and high conductivity according to claim 1, characterized in that In step 2, before the constant voltage electrochemical activation process is performed, the porous electrode support structure prepared in step 1 is first placed in anhydrous ethanol, acetone and deionized water in turn for ultrasonic cleaning, and finally dried.

6. The method for preparing a multi-scale porous electrode with high activity and high conductivity according to claim 1, characterized in that The constant voltage electrochemical activation process in step 2 is to place the porous electrode support structure in the electrolyte solution and use a three-electrode device to perform an in-situ electrochemical activation process on the surface of the porous electrode.

7. The method for preparing a multi-scale porous electrode with high activity and high conductivity according to claim 6, characterized in that In the three-electrode device described in step 2, graphite or carbon rod is selected as the counter electrode, Pt is used as the reference electrode, and the porous electrode support structure is used as the working electrode.

8. The method for preparing a multi-scale porous electrode with high activity and high conductivity according to claim 7, characterized in that The constant voltage electrochemical activation process described in step 2 applies a constant voltage of 1.38V to 1.47V, and the activation time is 4h to 6h.

9. The method for preparing a multi-scale porous electrode with high activity and high conductivity according to claim 1, characterized in that The drying temperature in step 2 is 60°C to 100°C.

10. The method for preparing a multi-scale porous electrode with high activity and high conductivity according to claim 9, characterized in that The drying time in step 2 is 2h.

Citation Information

Patent Citations

  • Three-dimensional porous electrode and preparation method and application thereof

    CN107394212A

  • Porous metal three-dimensional surface grinding flowing electro-deposition device and method for preparing coating through porous metal three-dimensional surface grinding flowing electro-deposition device

    CN109423671A

  • Smoothing the surface finish of rough metal articles

    US20200123675A1

  • Methods and systems for electrochemical additive manufacturing while modifying electrolyte solutions

    US20230089135A1